What Aspect of Dependence Does the Fagerström Test for Nicotine Dependence Measure?. (22nd November 2012) - DiFranza, Joseph R.; Wellman, Robert J.; Savageau, Judith A.; Beccia, Ariel; Ursprung, W. W. Sanouri A.; McMillen, Robert
Abstract : Although the Fagerström Test for Nicotine Dependence (FTND) and the Heaviness of Smoking Index (HSI) are widely used, there is a uncertainty regarding what is measured by these scales. We examined associations between these instruments and items assessing different aspects of dependence. Adult current smokers (n = 422, mean age 33.3 years, 61.9% female) completed a web-based survey comprised of items related to demographics and smoking behavior plus (1) the FTND and HSI; (2) the Autonomy over Tobacco Scale (AUTOS) with subscales measuring Withdrawal, Psychological Dependence, and Cue-Induced Cravings; (3) 6 questions tapping smokers' wanting, craving, or needing experiences in response to withdrawal and the latency to each experience during abstinence; (4) 3 items concerning how smokers prepare to cope with periods of abstinence. In regression analyses the Withdrawal subscale of the AUTOS was the strongest predictor of FTND and HSI scores, followed by taking precautions not to run out of cigarettes or smoking extra to prepare for abstinence. The FTND and its six items, including the HSI, consistently showed the strongest correlations with withdrawal, suggesting that the behaviors described by the items of the FTND are primarily indicative of a difficulty maintaining abstinence because of withdrawal symptoms.